Alex Delaware : Obsession - Book 21 - Kellerman, Jonathan (New York : Random House Large Print, 2007)
Phychologist Alex Delaware and LAPD detective Milo Sturgis investigate the aunt of a former patient, after she confesses to a crime shortly before she dies.
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Police -- California; Los Angeles; Fiction; Young women -- Fiction; Psychologists -- Fiction; Los Angeles (Calif.) -- Fiction; Psychological fiction; Large print books; Detective and mystery fiction